A decade of the anaphase-promoting complex in the nervous system - Huang, Ju (Genes Dev, 2016)
Control of protein abundance by the ubiquitin–proteasome system is essential for normal brain development and function. Just over a decade ago, the first post-mitotic function of the anaphase-promoting complex, a major cell cycle-regulated E3 ubiquitin ligase, was discovered in the control of axon growth and patterning in the mammalian brain. Since then, a large number of studies have identified additional novel roles for the anaphase-promoting complex in diverse aspects of neuronal connectivity and plasticity in the developing and mature nervous system. In this review, we discuss the functions and mechanisms of the anaphase-promoting complex in neurogenesis, glial differentiation and migration, neuronal survival and metabolism, neuronal morphogenesis, synapse formation and plasticity, and learning and memory. We also provide a perspective on future investigations of the anaphase-promoting complex in neurobiology.